Effects of judicial instructions and juror characteristics on interpretations of beyond reasonable doubt - Mueller-Johnson, Katrin (Psychology, crime & law, 2018)
The standard of proof, beyond reasonable doubt (BRD), serves as a threshold for reaching verdicts in criminal cases. Past research has demonstrated that factors such as the wording of judicial instructions defining the standard can influence people's interpretation of it. In addition, there is some concern that instructions may not be effective for the wider jury-eligible population. In an experimental study involving members of the general public, we examined the effect of two commonly used judicial instructions (i.e. sure and firmly convinced) against a situation when BRD was undefined, on people's quantitative interpretations of BRD as well as on their self-reported understanding of the standard and confidence in applying it. We also explored the effect of juror characteristics (i.e. gender, age and education). Compared to when the standard was undefined, the sure instruction helped to reduce inter-individual variability in interpretations of BRD and the firmly convinced instruction increased people's understanding of the standard. However, neither instruction was effective in increasing confidence in applying the standard or in reducing observed individual differences. These findings underscore the importance of developing evidence-based judicial instructions that can benefit the broad jury-eligible population equally and in a variety of ways.